Experimental and numerical investigation of air layer drag reduction on a flat plate - Salaheldin A. Mohamad; M. Youssef; Mohamed Bennaya; Khaled Elsherbiny (Alexandria Engineering Journal)
Reduction of Ship fossil fuel oil burning emissions has a significant impact to contain the global warming. Saving power by reducing ship resistance could basically reduce fossil fuel emissions. One of the most interesting techniques to reduce ship resistance is air lubrication drag reduction (ALDR). Motivated by those facts, an experimental study was carried out in Towing Tank using a flat plate by injecting air inside its bottom surface boundary layer and investigate the efficiency of this technique at different Froude numbers. A numerical model based on computational fluid dynamics (CFD) has been set up and validated to further investigate the air lubrication drag reduction phenomenon and explain the experimental observations. The results have revealed that the air lubrication efficiency is relatively contingent on the flow Reynolds number and hence to boundary layer thickness. It has been found that the turbulence effect assists the air layer to coexist with the transitional boundary layer. That eventually tends to cover more wetted surface area and achieve drag reduction up to 25 %. However, air lubrication within laminar flow ranges may cause a limited increase in total resistance.